QsvR and OpaR coordinately repress biofilm formation by Vibrio parahaemolyticus - Zhang, Miaomiao; Xue, Xingfan; Li, Xue; Wu, Qimin; Zhang, Tingting; Yang, Wenhui; Hu, Lingfei; Zhou, Dongsheng; Lu, Renfei; Zhang, Yiquan (Frontiers in Microbiology, 2023)
Mature biofilm formation by Vibrio parahaemolyticus requires exopolysaccharide (EPS), type IV pili, and capsular polysaccharide (CPS). Production of each is strictly regulated by various control pathways including quorum sensing (QS) and bis-(3ꞌ-5ꞌ)-cyclic di-GMP (c-di-GMP). QsvR, an AraC-type regulator, integrates into the QS regulatory cascade via direct control of the transcription of the master QS regulators, AphA and OpaR. Deletion of qsvR in wild-type or opaR mutant backgrounds altered the biofilm formation by V. parahaemolyticus, suggesting that QsvR may coordinate with OpaR to control biofilm formation. Herein, we demonstrated both QsvR and OpaR repressed biofilm-associated phenotypes, c-di-GMP metabolism, and the formation of V. parahaemolyticus translucent (TR) colonies. QsvR restored the biofilm-associated phenotypic changes caused by opaR mutation, and vice versa. In addition, QsvR and OpaR worked coordinately to regulate the transcription of EPS-associated genes, type IV pili genes, CPS genes and c-di-GMP metabolism-related genes. These results demonstrated how QsvR works with the QS system to regulate biofilm formation by precisely controlling the transcription of multiple biofilm formation-associated genes in V. parahaemolyticus.